2019
DOI: 10.1111/iwj.13205
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor vs platelet‐rich plasma: Activity against chronic wound microbiota

Abstract: The objective was to evaluate Staphylococcus aureus and Pseudomonas aeruginosa colonisation of wounds treated with recombinant epidermal growth factor (EGF) and platelet‐rich plasma (PRP); to analyse the susceptibility profiles of S. aureus and P. aeruginosa isolates from wounds treated with EGF and PRP; and to describe the presence of infection in EGF‐treated and PRP‐treated wounds. Experimental study was performed using clinical specimens collected with swabs. Patients were treated with PRP and EGF in the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A recent study on microbiome colonization showed that patients treated with EGF had no infections during the follow-up period, and there was a significant difference versus patients treated with PRP who had Staphylococcus aureus and Pseudomonas aeruginosa colonization ( P = 0.0078). [ 18 ] However, no patient in this study had infections either in PRP or rhEGF arm.…”
Section: Discussionmentioning
confidence: 84%
“…A recent study on microbiome colonization showed that patients treated with EGF had no infections during the follow-up period, and there was a significant difference versus patients treated with PRP who had Staphylococcus aureus and Pseudomonas aeruginosa colonization ( P = 0.0078). [ 18 ] However, no patient in this study had infections either in PRP or rhEGF arm.…”
Section: Discussionmentioning
confidence: 84%